The effects of acidity and aluminium leached from acidsulphate soils on riverine fish assemblages - Sutela, Tapio; Vehanen, Teppo (Boreal Environment Research Publishing Board, 2017)
Drainage of acid-sulphate soils mainly for agriculture, increases oxidation and leads to extensive leaching of acidity and aluminium (Al) to rivers in western Finland. The lowest average pH (4.55) values and the highest average Al concentrations (7.4 mg l–1) were measuredin the Vöyrinjoki, which appeared to be void of fish. Frequency of sites with no fish was clearly the highest (59%) in rivers with average pH < 5. Total fish density and biomass were the highest at the sites with pH > 6. The two fish species that are most tolerant to acidity, pike (Esox lucius) and perch (Perca fluviatilis), were found in rivers with an average pH as low as 4.6. Acid-sensitive species, especially grayling (Thymallus thymallus), brown trout (Salmo trutta) and minnow (Phoxinus phoxinus), were usually not found in rivers with average water pH < 6. To mitigate acidification of river waters, controlled farmland drainage techniques should be applied.